Serum peptides as putative modulators of inflammation in psoriasis. Issue 1 (July 2017) - Matsuura, Tetsuhiko; Sato, Masaaki; Nagai, Kouhei; Sato, Toshiyuki; Arito, Mitsumi; Omoteyama, Kazuki; Suematsu, Naoya; Okamoto, Kazuki; Kato, Tomohiro; Soma, Yoshinao; Kurokawa, Manae S.
Highlights: Patients with psoriasis possess specific serum peptide profiles. A fibrinogen α-derived peptide with 1462 m / z (p1462) increased in the psoriatic sera. p1462 increases the secretion of GROα from dermal microvascular endothelial cells. A filaggrin-derived peptide with 1977 m / z (p1977) increased in the psoriatic sera. p1977 decreases the secretion of GROα, IL-8, and MCP-1 from dermal endothelial cells. Abstract: Background: Psoriasis is a refractory inflammatory disease, however, its pathophysiology is still not fully understood. Objective: We tried to identify novel serum peptides associated with the pathophysiology of psoriasis. Methods: Serum peptides from 24 patients with psoriasis vulgaris (PV), 10 patients with psoriatic arthritis (PsA), 14 patients with atopic dermatitis (AD), and 23 healthy control (HC) subjects were analyzed by mass spectrometry. The effects of some peptides on the secretion of humoral factors from dermal cells were investigated by cytokine arrays and ELISAs. Results: A total of 93 peptides were detected. 24, 20, 23, and 2 peptides showed at least 1.2-fold difference in ion intensity between the psoriasis (PV + PsA) and HC groups, between the PV + PsA and AD groups, between the PV and PsA groups, and between patients with severe-to-moderate PV ( n = 6) and those with mild PV ( n = 18), respectively ( p < 0.05). 13 out of 27 peptides that showed at least 1.5-fold ion intensity difference in the abovementioned 4 comparisons were identified. The parent proteins of the identified peptides included a coagulation factor, proteins involved in the maintenance of skin, and a protein relating to cytoskeleton. We focused on 2 peptides that were increased in the PV + PsA group: a fibrinogen α chain-derived peptide (1462 m / z ), the unmodified form of which was fibrinopeptide A-des-alanine (FPAdA), and a filaggrin (FLG)-derived peptide (1977 m / z ), a modified form of FLG2099–2118 (Q2099 pE, Q2115 E; FLG-pEE). FPAdA stimulation increased the secretion of GROα from dermal microvascular endothelial cells (dMVECs) and decreased the secretion of lipocalin-2 from keratinocytes in comparison to FPAdA-resequenced peptide stimulation (GROα, 280.9 ± 7.3 pg/mL vs. 229.6 ± 5.0 pg/mL, p < 0.001; lipocalin-2, 273 ± 13 pg/mL vs. 350 ± 10 pg/mL, p < 0.01). Interestingly, FLG-pEE stimulation decreased the secretion of GROα, IL-8, and MCP-1 from dMVECs in comparison to FLG-derived control peptide stimulation (GROα, 844.3 ± 47.5 pg/mL vs. 1038.5 ± 96.9 pg/mL, p < 0.05; IL-8, 2240.1 ± 172.6 pg/mL vs. 3221.8 ± 523.7 pg/mL, p < 0.05; MCP-1, 4057.8 ± 157.2 pg/mL vs. 4619.1 ± 213.4 pg/mL, p < 0.05). Conclusions: The results suggested that some serum peptides are involved in the pathophysiology of psoriasis, regulating the secretion of inflammatory chemokines and an antimicrobial protein. The modulation of serum peptides may be a potential therapeutic strategy for psoriasis.